Nurses' experiences of inpatients suicide in a general hospital* - Mirriam Matandela; Mokgadi C. Matlakala (AOSIS, 2016)
When suicide occurs, it is regarded as an adverse event. Often, little attention is given to the nurses who cared for the patients prior to the adverse event. Instead the affected nurses are expected to write statements and incident reports about the adverse event. The aim was to explore the experiences of nurses who cared for patients who successfully committed suicide whilst admitted at a specific general hospital in Gauteng Province, South Africa. A qualitative exploratory research was conducted. Data were collected through in-depth interviews with a purposive sample of six nurses and content analysis was done. Nurses experienced feelings of shock; blame and condemnation; inadequacy and feared reprisal. This study suggests a basis for development of support strategies to assist the nurses to deal with their emotions following experience of adverse events.